Effect of phosphorus and sulphur fertilization on productivity and nutrient uptake of pigeonpea (Cajanus cajan) - Kumar, Sudhir; Kumar, Subodh; Singh, Omkar; Singh, B.P. (Annals of Agricultural Research, 2014)
A field experiment was conducted at Baraut (U.P.) to study the effect of phosphorus and sulphur fertilization on pigeonpea during kharif season of 2008 and 2009. Application of 80 kg P2O5/ha and 60 kg S/ha with PSB inoculation significantly improved growth and yield attributes and seed yield of pigeonpea. Uptake of N, P, K and S also increased with application of phosphorus (up to 80 P2O5/ha) and sulphur (up to 60 kg S/ha) and PSB inoculation. Mean increases in seed and straw yield with 80 kg P2O5 ha-1 were 27.72 and 14.10%, respectively, over control. Similarly, 30 kg S ha-1 increased the seed and straw yield by 21.02 and 10.20%.